A sensitive molecular imprinted surface plasmon resonance nanosensor for selective determination of trace triclosan in wastewater - Atar, N.; Eren, T.; Yola, M.; Wang, Shaobin (Elsevier, 2015)
Triclosan (TCS) has been widely used as an antibacterial and antifungal agent in household cleaning and personal care products. The widespread use of TCS in the cleaning products poses a potential risk to the ecological system and human health due to its release into sediments, wastewater and ground water resources causing chronicle toxicity to aquatic organisms. However, no simple method is available for its detection and quantitative determination in aqueous solution. A novel molecular imprinted surface plasmon resonance (SPR) chemical sensor was developed for sensitive and selective detection of triclosan (TCS) in wastewater, using allylmercaptane modified gold SPR chip and imprinted poly(2-hydroxyethyl methacrylate–methacryloylamidoglutamic acid) [p(HEMAGA)] nanofilm. The unmodified and imprinted surfaces of the SPR chip were characterized by Fourier transform infrared (FTIR) spectroscopy, atomic force microscopy (AFM) and contact angle measurements. The developed sensor was validated according to the ICH guideline (International Conference on Harmonisation). The linearity range and detection limit of TCS were obtained as 0.05–1.0 ng/mL and 0.017 ng/mL, respectively. The developed molecular imprinted nanosensor was successfully applied to wastewater samples for the determination of TCS and exhibited excellent performance.